(untitled) (Medico Legal Update, 2021)
Background: The ability to assess kidney function properly has important health implications. Glomerular filtration rate (GFR) is still accepted as the best measurement index of kidney function. The formula of the Modified of Diet in Renal Disease (MDRD) is currently widely used by the medical community to estimate GFR (estimated GFR or eGFR). The renogram with radiofarmaka I131-Hippuran is considered to have an inherent accuracy of inulin cliren as the gold standard of GFR measurement. Objective: To determine the description of renogram and eGFR’s results in assessing kidney function of CKD patients. Method: This study was a retrospective observational that used medical records from 113 CKD patients undergone renogram examination at Dr. Soetomo General Hospital Surabaya in 2012. eGFR was calculated based on the serum creatinine, age, and sex of the patient. Data of renogram and eGFR examination were presented descriptively. Results: We obtained male of 63% and female of 37% with age range between 20-69 years. The highest percentage in the age range of 50-59 years. The CKD cases in this study were mostly caused by urinary tract stones of 44%. The most common renogram results were 2 kidney failure by 48% and the highest eGFR was <15 ml/min/1.73m2 score of 73%. Conclusion: There were no normal results of renogram or eGFR. The most renogram results with 2 kidney failure were found in 48% of all aubjects with eGFR of <15 ml/min/1.73m2.